Validation of Multiple Solute Model for Application to Micellar Enhanced Ultrafiltration and Comparison with Modified Resistance in Series Model - Pawar, S.K.; Marathe, K. V. (Journal of Applied Solution Chemistry and Modeling, 2013)
<!--[if gte mso 9]> <![endif]--> Modified resistance in series model and multiple solute models have been studied for its application in micellar enhanced ultrafiltration (MEUF). Experimental results for separation of Ni(II) ions from synthetic wastewater with anionic surfactant sodium dodecyl sulfate (SDS) and nonionic surfactant Tween 80 are used for validation of mathematical models. Modified resistance in series model is characterized by model parameters such as specific resistance Î±0, membrane resistance Rm and mass transfer coefficient k. Whereas, multiple solute model is characterized by the parameters such as membrane resistance Rm, permeability coefficient Pm, back transport coefficient Kbi and mass transfer coefficient ki for each solute in the system. These parameters are estimated by using the Levenberg-Marquardt method coupled with the Gauss-Newton algorithm using MATLAB. The simulation results for multiple solute model are in good agreement with the experimental results as compared to the simulation results obtained by using modified resistance in series model. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->